A Strategy for Leveraging Key Opinion Leaders to Increase Brand Awareness for Photoplace Indonesia - Fitria, Nur Indah; Hadiyanto, Hadiyanto (Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of the creative industry has increased competition in the photobox business in Indonesia. This situation requires photobox service providers to implement more innovative marketing strategies that are relevant to current trends. Photoplace Indonesia, as one of the modern photobox providers, strives to increase brand awareness through digital marketing strategies, particularly by utilizing collaborations with key opinion leaders (KOLs) who are effective in reaching young audiences on social media. This study aims to analyze the strategy of utilizing KOLs in building brand awareness for Photoplace Indonesia, identify supporting factors that are indicators of campaign success, and identify inhibiting factors that can affect the smooth implementation. The research method used a qualitative approach through direct observation, interviews with the marketing communications team, participation during internship activities, and literature studies related to marketing strategies, KOLs, and brand awareness. Based on the findings, the KOL utilization strategy was carried out through appropriate KOL selection, systematic brief preparation, coordination during the content production process, and evaluation of campaign performance based on indicators such as engagement and audience response. Supporting factors included strategic planning, maximum utilization of social media platforms, and good internal communication, while inhibiting factors included limited local KOLs, variations in content production capabilities, and technical constraints at outlets. Overall, collaboration with KOLs was proven to increase message reach, digital interaction, and brand awareness at Photoplace Indonesia.